T45. Effects of fampridine administration on central motor conduction failure in multiple sclerosis patients. (May 2018) - Di Sapio, Alessia; Giorgi, Stefano; Bertolotto, Antonio; Sperli, Francesca; Melillo, Federica; Troni, Walter
Abstract : Introduction: Fampridine is a slow-release potassium channel blocker that ameliorates the impaired conduction in CNS demyelinated axons. In multiple sclerosis (MS) patients, wide fluctuations in fatigue perception make difficult to assess the highly variable clinical response to treatment. Previous study reported that central motor conduction time (CMCT) improvement may predict fampridine response. Nevertheless, more than conduction slowdown, central motor conduction failure (CMCF), i.e. conduction block and axonal damage, reflects walking impairment in MS patients. Decrease of Motor Evoked Potentials (MEP) area, much more than amplitude, may detect CMCF. Serial MEP area recordings and analysis, according to a protocol that reduces MEP area random variability, may detect CMCF variation. We evaluated the effects of fampridine on CMCT and CMCF by serial recordings of MEPs from several proximal and distal muscle districts of lower limbs in a MS patients cohort and we correlated the obtained data with clinical outcome. Methods: In 10 MS patients, MEPs to TMS by double-cone coil and maximal Compound Motor Action Potentials (CMAPs) to High Voltage Electrical Stimulation of lumbosacral roots were recorded from Vastus Medialis and Lateralis, Tibialis Anterior, Peroneus Longus and Flexor Hallucis Brevis of both limbs (T1) according to the published method (Di Sapio et al., 2014). Stimulation and recorded sites were marked. In 3 patients the test was repeated after one week (T1b), as control. After 14 days of fampridine treatment, before stopping therapy (T2), the procedure was repeated, strictly maintaining the same stimulation and recording sites and stimulation intensities. The 25-foot walking test (25FWT), 6-min walking test (6'-WT), the Fatigue Score Scale (FSS) and the Modified Fatigue Inventory Scale (MFIS) were administered at each time point. In each patient CMCT, MEP area and MEP Area/CMAP area ratios (ARs) were compared, and if appropriate their variability normalized according to Troni et al. (2016). Patients were classified as neurophysiological responders when 2 or more area/latency indexes significantly improved, remaining the others stable. Moreover, pooled data from the whole cohort in different time-points were compared using T test (Wilcoxon). Results: CMCT, MEP area and AR did not change significantly in patients not receiving fampridine. After fampridine administration 3 patients were classified as responders; the same patients reported fatigue reduction and showed significant improvement in FSS score and 25FWT, while MFIS and 6'WT improved only in 1 patient. By analysing pooled data obtained from responders only, a significant reduction of CMCT ( p  = 0.0057) and increase in MEP area ( p  = 0.0014) and AR ( p  = 0.048) were noted. Conclusion: The CMCF evaluation, together with CMCT, both made more sensitive by adopting multiple recording sites, correlate with self-reported and clinical outcome of fampridine treatment and may help to clarify doubt cases.